Primary carnitine deficiency: novel mutations and insights into the cardiac phenotype. (12th March 2013) - Shibbani, K.; Fahed, A.C.; Al‐Shaar, L.; Arabi, M.; Nemer, G.; Bitar, F.; Majdalani, M.
<x xml:space="preserve">Abstract</x> Solute carrier family 22 member 5 (SLC22A5) encodes a sodium‐dependent ion transporter responsible for shuffling carnitine across the plasma membrane. This process provides energy for the heart, among other organs allowing beta‐oxidation of fatty acids. Mutations in SLC22A5 result in primary carnitine deficiency (PCD), a disorder that manifests with cardiac, skeletal, or metabolic symptoms. We hereby describe two novel mutations in SLC22A5 in two Lebanese families associated exclusively with a cardiac phenotype. The frequency of the cardiac, metabolic and skeletal symptoms in PCD patients remains undefined. All the reported eight PCD patients belonging to five different Lebanese families have an exclusive cardiac phenotype. Carnitine levels appear to be directly linked to the type and position of the mutation and the severity of the phenotypic presentation does not seem to be associated with serum carnitine levels. A comprehensive review of 61 literature‐reported PCD cases revealed an exclusive cardiac manifestation frequency at 62.3% with a very low likelihood of simultaneous occurrence of cardiac and metabolic manifestation.